2021
DOI: 10.3390/met11060962
|View full text |Cite
|
Sign up to set email alerts
|

Role of Non-Metallic Inclusions in the Fracture Behavior of Cold Drawn Pearlitic Steel

Abstract: In this paper an exhaustive scientific work is performed, by means of metallographic and scanning electron microscope (SEM) techniques, of the microstructural defects exhibited by pearlitic steels and their evolution with the manufacturing process by cold drawing, analyzing the consequences of such defects on the isotropic/anisotropic fracture behavior of the different steels. Thus, the objective is the establishment of a relation between the microstructural damage and the fracture behavior of the different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…To prevent material regions with a high concentration of nonmetallic inclusions, as reported in the literature, [10,22,23] the machined specimens were obtained from the midsize position between the center and edges of the rolled bar (Figure 1c). Surface grinding and polishing operations were applied to the machined specimens with medium size wheel grit and diamond paste of 3 and 1 μm.…”
Section: Materials Specimens and Methodsmentioning
confidence: 99%
“…To prevent material regions with a high concentration of nonmetallic inclusions, as reported in the literature, [10,22,23] the machined specimens were obtained from the midsize position between the center and edges of the rolled bar (Figure 1c). Surface grinding and polishing operations were applied to the machined specimens with medium size wheel grit and diamond paste of 3 and 1 μm.…”
Section: Materials Specimens and Methodsmentioning
confidence: 99%
“…Toribio et al [5] showed the importance of detailed metallographic and scanning electron microscope (SEM) microstructure analysis of microstructural defects exhibited by pearlitic steels in order to unveil how their evolution by cold drawing has consequences on the isotropic/anisotropic fracture behavior of different steels. Such defects caused by non-metallic inclusions have a very relevant role in the fracture behavior of cold drawn pearlitic steels [5]. Papadopoulou et al [6] also present the importance of advanced microstructure analysis in understanding microstructure evolution and optimizing mechanical behavior.…”
Section: Contributionsmentioning
confidence: 99%
“…The control of inclusions is not only limited to the refining [12][13][14][15][16][17] and solidification processes [18][19][20], but also needs to pay attention to the evolution behavior of inclusions in the hot working process [21]. And in the study of steel samples, it was also found that there are hard, high-melting-point Al 2 O 3 inclusions.…”
Section: Introductionmentioning
confidence: 99%